Estimates of the genetic parameters, optimum sample size and conversion of quantitative data in multiple categories for soybean genotypes - doi: 10.4025/actasciagron.v34i3.14015 - Éder Matsuo; Tuneo Sediyama; Cosme Damião Cruz; Rita de Cássia Teixeira Oliveira; Luiz Renato Cadore (Acta Scientiarum. Agronomy, 2011)
The objective of this study was to estimate the genetic parameters and optimal sample size for the lengths of the hypocotyl and epicotyls and to analyze the conversion of quantitative data in multiple categories for soybean genotypes. A total of 85 soybean genotypes were analyzed in four experiments in a completely randomized design under greenhouse conditions at the Federal University of Viçosa, Brazil. The magnitude of the genetic parameter estimates characterized the influence of the genetic components in the phenotypic expression of the length of the hypocotyls and epicotyls of different soybean genotypes. The optimal size of the sample varied between the genotypes and the conversion of the quantitative data in multiple categories provided estimates of correlation coefficients greater than 0.80 and coincidence greater than 81% between the converted data and the original data.